2008
DOI: 10.1002/ird.388
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hysteresis and rainfall intensity on finger dynamics

Abstract: The purpose of this paper is to present sand-box experiments and a hysteresis model to explain the formation and hydraulic properties of fingered flow. Previous researches have found that a fingered path persists over long periods of constant infiltration; hysteresis could be an important factor. In this paper, a major point is to utilize the boundary and series internal scanning curves of the hysteresis model derived by Huang et al. (2005) to clearly obtain the variations between soil water content (u) and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
2
1
0
Order By: Relevance
“…Studies focusing on the formation of finger-shaped flow paths found the finger width to be influenced not only by soil properties and initial and bound-ary conditions (Glass et al, 1989) but also by the flow rate through the finger (Parlange and Hill, 1976;White et al, 1976), with higher flow rates leading to an increase in finger width. This was also observed by Ma et al (2008), who also found a positive correlation between rainfall intensity, time of finger flow occurrence, and mean velocity. The increase in mean velocity of the fingers leads to a faster downward transport and thus deeper infiltration depths with higher irrigation intensities (Cremer et al, 2017).…”
Section: Impact Of Irrigation Intensitysupporting
confidence: 78%
“…Studies focusing on the formation of finger-shaped flow paths found the finger width to be influenced not only by soil properties and initial and bound-ary conditions (Glass et al, 1989) but also by the flow rate through the finger (Parlange and Hill, 1976;White et al, 1976), with higher flow rates leading to an increase in finger width. This was also observed by Ma et al (2008), who also found a positive correlation between rainfall intensity, time of finger flow occurrence, and mean velocity. The increase in mean velocity of the fingers leads to a faster downward transport and thus deeper infiltration depths with higher irrigation intensities (Cremer et al, 2017).…”
Section: Impact Of Irrigation Intensitysupporting
confidence: 78%
“…As stated by Viaene et al (1994)‘In those cases, the model presented by Parlange (1976) seems to be the best choice’. This conclusion seems to hold in more recent studies (Si & Kachanoski, 2000; Ma et al , 2008). Mualem & Beriozkin (2009) agree with the conclusion of Viaene et al (1994) when using the main drying curve for a one‐branch model.…”
supporting
confidence: 52%
“…The model can describe the main curves and internal scanning curves of WRC regarding both of the wetting and drying processes. It also is applicable for explaining the finger flow phenomenon in sand box experiments (Ma et al ., ), as well as modelling the soil moisture variation (Tan et al ., ).…”
Section: Infiltration Patterns Of Sand With Different Porositiesmentioning
confidence: 99%